Immunogenic proteins in dermatophyte mycelial extracts - Drobnič-Košorok, Marinka (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 1998)
Background. Dermatophyte cytosolic proteins and cell wall proteins as well different metabolites secreted by fungi are known to be involved in eliciting humoral and cellular immune response in invaded host. Methods. SDS-PAGE and Western blot techniques were used to study the imunogenic nature of the cytosolic proteins extracted from two dermatophyte species Microsporum canis and Trichophyton mentagrophytes and two non dermatophyte fungal species Malassezia pachydermatis and Aspergillus fumigatus. Crossreactivity was confirmed with ELISA technique. Results. SDS-PAGE analysis of cytosolic proteins revealed several protein bands, which are common to the dermatophytesexamined, together with some distinctive bands, which enabled us to discriminate between the dermatophyte species. However, comparison of the cytosolic protein profile obtained from dermatophytes and nondermatophyte fungi studied demonstrated a much higher extent of species-specific proteins. The crossreactivity nature of the investigated fungal antigens was observed inELISA, and developed for the detection of specific IgG in cats infected withMicrosporum canis. Conclusion. Besides strongly crossreacting antigenic protein bands, Western blot analysis, using the same serum samples as in ELISA, also disclosed species-specific immunogenic proteins, which may be the candidates for further investigation of cellular immune response and development o protective vaccines.
Keywords: Analysis; Aspergillus fumigatus; Blotting, western; Cats; dermatofiti; dermatologija; Dermatophytes; diagnostika; Electrophoresis, polyacrylamide gel; Enzyme-linked immunosorbent assay; Fungal proteins; Immunology; Malassezia; Microsporum; mikrosporija; Trichophyton; veterinarstvo